Une VAE à l'université, et après ? - Gilles Pinte
The validation of non formal and informal learning (VNIL) is a device which takes into account the non formal and informal education acquired by a person. The VNIL was conceived as a fourth certification path on the same level as initial training or continuing education or apprenticeship. After ten years of development, many aspects of VNIL have been studied by researchers : the analysis of candidate's motivation, the analysis of experience, the notion of conseling or guidance in the validation process... Few researches have focused on the effects after the candidate is qualified, that is to say the effects of VNIL on career development, wages or re-employment. To enlight the effects we propose in this article the results of a survey including 223 university applicants who have completed a VNIL procedure for diplomas from undergraduate to graduate.